Total consumer time: A new approach to identifying digital gatekeepers - Niklas Gösser; Kaan Gürer; Justus Haucap; Bernd Meyring; Asimina Michailidou; Martin Schallbruch; Daniela Seeliger; Susanne Thorwarth (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
[Introduction:] The route to customers is becoming increasingly digital, for any business. There is hardly any business that is not focussing on reaching customers online. The Covid-19 pandemic has further accelerated this trend. In many markets, digital platforms have become essential tools for the sale of goods and services. On the one hand, there are transaction platforms for specific goods and services. They are specialist providers in their fields. Consumers access the relevant specialist to directly search for the product or service they intend to purchase, and they expect to directly conclude transactions on the platform ("transaction platforms"). These platforms typically generate the majority of their revenues from sales to consumers or commissions from these sales. On the other hand, there are attention platforms that provide information, entertainment and/or other services (e-mail accounts, translations, search functionality, social media contacts, software use, etc.) to users ("attention platforms"). These platforms are often free of charge for consumers and they generate most of their revenues from advertising. In order to maximize revenues these platforms often aim at maximizing the time that consumers spend within their ecosystems so as to channel consumers' attention to advertising clients or - in case of vertical integration - also to their own offerings. Through the selection of content such as ranking search results and also through advertising these attention platforms can have significant impact on which products receive consumer attention in the first place which enables them to affect and even steer competition. If platforms have such a significant effect on consumer attention that they can steer consumers towards some products and away from others, they may factually become a gatekeeper for these markets. (...)
Keywords: 330; Social Web; Online-Handel; Online-Marketing; Konsumentenverhalten; Netzwerkökonomik